COMPARING TWO ANALYTICAL MODELS FOR ORBIT DETERMINATION USING GPS NAVIGATION SOLUTIONS - Kuga, Hélio K.; Lopes, Rafael A. M. (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
This work presents the results of two analytical orbit models for orbit determination using the navigation solutions provided by on-board GPS receivers. Herein one proposes toÂ analyze two analytical orbit models that can be used both on-board and on ground controlÂ centers for quick orbit determination. One model is the NORAD SGP8 elements (Hoots and Roehrich, 1980) where the two-line elements (TLE) are the orbit data needed to compute orbits. The second one is the analytical orbit model of the CBERS (China-Brazil EarthÂ Resources Satellite) mission named COE (CBERS Orbit Elements). The orbit determinationÂ (OD) system to generate the TLE and COE datasets is being developed to be implemented inÂ the INPE (Brazilian Institute for Space Research) ground control center. The TLE may beÂ disseminated regularly to allow image receiving ground stations to track the CBERS-4 satellite. The COE can be used in the control center to monitor the orbit and computeÂ maintenance maneuvers. The paper describes the basics of the two models, and implementsÂ such models to fit in the least squares sense the GPS long arc navigation solutionÂ measurements. Results will be shown based on actual GPS measurements from CBERSÂ satellites, comparing aspects of the fittings and the models propagation. Â Keywords: Orbit determination, GPS Navigation Solution, CBERS Orbit Elements, Two-LineÂ Elements